In vitro antibacterial effects of Broussonetia papyrifera leaf extract and its anti-colitis in DSS-treated mice - Liang, Xiaoxiao; Ru, Meng; Zhai, Zhenya; Huang, Jianzhen; Wang, Wanwan; Wang, Ruxia; Zhang, Zhihong; Niu, Kai-Min; Wu, Xin (Frontiers in Cellular and Infection Microbiology, 2023)
Recently, the hybrid Broussonetia papyrifera (BP) has been extensively cultivated and predominantly utilized in ruminants because of its high protein and bioactive compound content. In the present study, the effects of an ethanolic extract of BP leaves (BPE, 200 mg/kg) on mitigating 2% dextran sodium sulfate (DSS)-induced intestinal inflammation in mice were evaluated. BPE is rich in flavonoids, polyphenols, and polysaccharides, and displays potent antioxidant and antibacterial activities against pathogenic strains such as Clostridium perfringens, Salmonella Typhimurium, and Salmonella enterica subsp. enterica in vitro. In a mouse study, oral administration of DSS resulted in weight loss, incidence of diarrhea, enlargement of the liver and spleen, impaired colonic morphology, downregulation of both gene and protein expression related to intestinal antioxidant (Nrf2) and barrier function (ZO-1), decreased diversity of colonic microbiota, and 218 differentially altered colonic metabolites; however, co-treatment with BPE did not restore these modified aspects except for the liver index and colonic bacterial diversity. The singular treatment with BPE did not manifest evident side effects in normal mice but induced a mild occurrence of diarrhea and a notable alteration in the colonic metabolite profile. Moreover, a single BPE administration augmented the abundance of the commensal beneficial bacteria Faecalibaculum and Akkermansia genera. Overall, the extract of BP leaves did not demonstrate the anticipated effectiveness in alleviating DSS-induced intestinal inflammation.